A review of two thousand years of traditional medicine in Cajamarca, Peru: historical use of medicinal plants - Silva, W. (2025)
Background: In Peru, knowledge of traditional medicine dates back to pre-Inca times, such as “Cupisnique”, in northern Peru, where a complex system of traditional medicine was developed. With the arrival of the Spanish in Cajamarca in 1532, attempts were made to suppress these practices through evangelization; however, cultural resistance and the vastness of the territory favored their persistence, also integrating European elements. Methods: A systematic review was conducted in scientific databases with broad coverage, such as Google Scholar and Web of Science (WOS), supplemented by physical libraries, with the aim of systematizing information related to the historical use and trade of medicinal plants in the department of Cajamarca, Peru. Results: Results: The cultures that inhabited the Cajamarca valleys already practiced healing or shamanism, a tradition that has endured to the present day. During the colonial period, attempts were made to restrict traditional medicine, although species such as cinchona (Cinchona spp.) proved their therapeutic value. In the early and middle republican periods, interest was limited, but inventories and botanical studies were carried out. In the contemporary period, research in various scientific disciplines stands out. Markets supply Cajamarca and the Peruvian coast with medicinal plants, mainly of wild origin. Conclusions: In the department of Cajamarca, the use of medicinal plants and traditional medicine originated in pre-Inca times and has endured throughout history. Today, it is reinforced by scientific contributions that highlight its cultural therapeutic, and economic value. It also plays a strategic role in supplying medicinal plant species to markets.